A Systematic Literature Review on Religiosity : The Social and Economic Determinants of Religious Intensification - Muntaqo, Lutfan; Hidayah, Atinia; Kaukab, M. Elfan; Jusoh, Wan Noor Hazlina Wan (Jurnal Lektur Keagamaan, 2024)
Religion plays a vital role in human life, yet many studies focus on its consequences rather than the factors influencing religiosity and religious intensification. This study examines the social and economic determinants that shape religious faith through a literature review of 25 relevant studies from the Scopus database. The findings reveal that social factors predominantly drive religious intensification. These factors include the family environment (parental religiosity, closeness to parents), socialization (religious exposure in childhood), and social conditions (trauma, religious freedom, and societal attitudes). Social demographics such as gender, age, and marital status also play a role. Conversely, economic factors tend to negatively influence religious practices. These factors include income levels (relative and absolute), macroeconomic conditions (GDP per capita, trade volume, and travel costs), socio-economic status (employment, education, and social insurance), and economic development in countries of origin and destination. The study highlights the complex interplay between social and economic factors in shaping religiosity and religious intensification. These findings underscore the need for policies that balance social and economic considerations, promote religious pluralism, and address societal vulnerabilities to foster inclusive approaches to managing religious dynamics in diverse communities.